2016
DOI: 10.1093/hmg/ddw153
|View full text |Cite
|
Sign up to set email alerts
|

Meckel’s and condylar cartilages anomalies in achondroplasia result in defective development and growth of the mandible

Abstract: Activating FGFR3 mutations in human result in achondroplasia (ACH), the most frequent form of dwarfism, where cartilages are severely disturbed causing long bones, cranial base and vertebrae defects. Because mandibular development and growth rely on cartilages that guide or directly participate to the ossification process, we investigated the impact of FGFR3 mutations on mandibular shape, size and position. By using CT scan imaging of ACH children and by analyzing Fgfr3Y367C/+ mice, a model of ACH, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…For example, in the Fgfr3-K644E mouse model, enhanced proliferation of chondrocytes was detected in the growth plate during a limited period in the early stages of endochondral ossification, whereas a decreased chondrocyte differentiation was observed all along the bone development (19). A similar conclusion was made in the Fgfr3-Y367C mouse model for the growth plate and for Meckel's cartilage (20,21). In our study, we observed this increase of proliferation at birth; this latter could, however, also occur during a limited period but cannot be detected because Adamtsl2 KO mice die at birth.…”
Section: Discussionsupporting
confidence: 54%
“…For example, in the Fgfr3-K644E mouse model, enhanced proliferation of chondrocytes was detected in the growth plate during a limited period in the early stages of endochondral ossification, whereas a decreased chondrocyte differentiation was observed all along the bone development (19). A similar conclusion was made in the Fgfr3-Y367C mouse model for the growth plate and for Meckel's cartilage (20,21). In our study, we observed this increase of proliferation at birth; this latter could, however, also occur during a limited period but cannot be detected because Adamtsl2 KO mice die at birth.…”
Section: Discussionsupporting
confidence: 54%
“…However, it is not yet known whether Fgfr2 is solely responsible for FGF-mediated regulation of Scx + /Sox9 + cells. Fgfr1 and Fgfr3 are restricted to chondroblastic and hypertrophic layers within the postnatal condylar cartilage and Fgfr3 signaling regulates chondrocyte maturation in the condyle (Duplan et al, 2016;Fuentes et al, 2002;Yasuda et al, 2012). Thus, these FGFR family proteins have the potential to regulate eminence formation within the tendon-bone attachment units of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Fgf18 disruption causes defective calvarial development (Ohbayashi et al, ). Both Fgfr3 inactivation and overactivation can lead to skeletal abnormalities in craniofacial regions (Biosse Duplan et al, ; Yu et al, ). In this study, we took advantage of Dmp1 Cre and R26R Fgf8 mice to activate FGF8 signaling in osteocytes during embryonic development.…”
Section: Discussionmentioning
confidence: 99%